Stratifikasi Sosial Ditinjau dari Aspek Santri dan Bukan Santri Di Desa Wargabinangun Kabupaten Cirebon - Eddy Saputra (SAP (Susunan Artikel Pendidikan), 2018)
This research is conducted on a social stratification among the community, namely between santri (Islamic student) and non-santri. Even though such stratification has long been abolished since Islam existed among the Arabs in the past time, it in fact still exists in Indonesian society whose people practically understand religious knowledge. The research is expected to provide us information reminding us of the equivalence of human beings before God. The research uses a qualitative method, by which the data are collected from direct observation, interviews with santri, non-santri, and informants including village leaders and from other data sources. The data are analyzed in three simultaneous lines of activities consisting of  data reduction, data presentation, data verification and are then matched to the occurrences in the field